Synthesis and preliminary study of pure and Zr-doped YMnO3 compounds as Solid Oxide Fuel Cells electrode - Moreno Botello, Zulma Liliana (2017)
The Y1−xZrxMnO3series (0 ≤ x ≤ 0.30) has been studied to be used as possible SOFC electrode material. These compounds adopt a layered structure of hexagonal symmetry in which the manganese cations are located in trigonal bi-pyramidal coordination of oxygen atoms, different from that of the classical perovskite. The synthesis of the materials has been carried out by solid state reaction and X-ray diffraction technique reveals that pure phases can be obtained until x∼0.10. For x ≥ 0.10, an additional YSZ phase is formed, similar to the SOFC electrolyte material. HT-XRD technique and thermogravimetric analysis of pure or Zr-doped YMnO3indicate that, in diluted dry H2for T > 600 °C, these compounds are unstable, what precludes their use as anode material. On the other hand, reactivity studies at high temperature (T = 1300 °C) between Y1−xZrxMnO3(x = 0, 0.05 and 0.1) and 8YSZ show a chemical compatibility in which the formation of an electrically insulating phase does not take place, but a crossed diffusion of Y3+/Mn3+and Zr4+at the interface between both materials. Thermomechanical compatibility in air between YSZ and Y1−xZrxMnO3is also demonstrated from RT to 850 °C.